Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT Delamibrands Kharisma Busana Kota Tangerang - Alfitho Afifi; Jeni Andriani (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The purpose of this study was to determine the effect of Work Motivation and Work Discipline on Employee Performance of PT Delamibrands Kharisma Busana Tangerang City. This research uses associative methods with quantitative techniques. The sampling technique used was purposive sampling, totaling a sample of 76 respondents. The data analysis techniques used are data instrument test, classical assumption test, descriptive analysis, quantitative analysis and hypothesis testing. The result of this study is that Work Motivation affects Employee Performance with a correlation coefficient of 0.589 having a moderate level of relationship. Hypothesis testing obtained tcount> ttable or (6.277> 1.993) thus H₀ is rejected and H₁ is accepted, meaning that there is a partial influence between Work Motivation variables on Employee Performance at PT Delamibrands Kharisma Busana Tangerang City. Work Discipline affects Employee Performance with a correlation coefficient of 0.329 having a weak level of relationship. Hypothesis testing obtained tcount> ttable or (2.994>1.993) thus H₀ is rejected and H₁ is accepted, meaning that there is a partial influence between the Work Discipline variable on Employee Performance at PT Delamibrands Kharisma Clothing Tangerang City. Work Motivation and Work Discipline affect Employee Performance with a correlation coefficient of 0.601 having a moderate level of relationship. Hypothesis testing obtained Fcount> Ftabel or (20.654> 3.12) thus H₀ is rejected and H₁ is accepted, meaning that there is a simultaneous influence between the variables of Work Motivation and Work Discipline on Employee Performance at PT Delamibrands Kharisma Busana Tangerang City.